Pengembangan Perangkat Pembelajaran Berbasis Higher Order Thinking Skill (HOTS) - Joan Shelomikha Mawikere; Vivian E. Regar; Marvel G. Maukar (Departement of Mathematics Education, 2023)
Joan Shelomikha Mawikire. 19504045. Development of High Order Thinking Skill (HOTS) Based Learning Tools. Mathematics Department. Faculty of Mathematics, Natural and Earth Sciences. Manado State University. Tondano 2023. The aim of this research is to develop learning tools based on Higher Order Thinking Skill (HOTS) on tube material in class VII A of SMP Negeri 1 Tondano. To see the quality of the development of this learning tool, it is seen from three aspects, namely validity, practicality and effectiveness. This type of research is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. According to the validity aspect, the expert validator's score for the teaching module was 94 with very valid criteria and for the Student Worksheet (LKPD) the score was 92 with very valid criteria. According to the practical aspect, assessment is seen from the teacher's response and the student's response. The assessment score obtained from the teacher's response was 96 with very good criteria and the assessment score for student responses was 88 with very good criteria. According to the effectiveness aspect, the learning tools developed are effective as seen from the completion of the student learning outcomes test, which is 81%. So the results of this research are the learning tools developed that are valid, practical and effective for use in learning.